2008
DOI: 10.1039/b806979b
|View full text |Cite
|
Sign up to set email alerts
|

Solving the Schrödinger equation of helium and its isoelectronic ions with the exponential integral (Ei) function in the free iterative complement interaction method

Abstract: We introduce here the exponential integral (Ei) function for variationally solving the Schrödinger equation of helium and its isoelectronic ions with the free iterative complement interaction (ICI) method. In our previous study [J. Chem. Phys., 2007, 127, 224104], we could calculate very accurate energies of these atoms by using the logarithmic function as the starting function of the free ICI calculation. The Ei function has a weak singularity at the origin, similarly to the logarithmic function, which is imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…In the FC method, such explicit r 12 dependence is automatically generated in the ICI step and, therefore, the FC wave function shows quite excellent convergence to the exact wave function. This has actually been shown previously for the helium atom, giving highly accurate energy, wave function, and properties 19, 21, 23, 24. More recently 25, we have further examined the local energy, H‐square error, and energy upper and lower bounds using the FC wave function of the helium atom and shown the highly accurate nature of the FC wave function.…”
Section: Electron–nucleus and Electron–electron Cusp Conditions For Tsupporting
confidence: 71%
See 2 more Smart Citations
“…In the FC method, such explicit r 12 dependence is automatically generated in the ICI step and, therefore, the FC wave function shows quite excellent convergence to the exact wave function. This has actually been shown previously for the helium atom, giving highly accurate energy, wave function, and properties 19, 21, 23, 24. More recently 25, we have further examined the local energy, H‐square error, and energy upper and lower bounds using the FC wave function of the helium atom and shown the highly accurate nature of the FC wave function.…”
Section: Electron–nucleus and Electron–electron Cusp Conditions For Tsupporting
confidence: 71%
“…Since 1999, one of the authors has been involved in this difficult task and has published a series of articles to formulate a general method of solving the SE of atoms and molecules in an analytical expansion form 7–25. First, he clarified the mathematical structure of the exact wave function and proposed a method, called the iterative complement (or configuration) interaction (ICI) method that gives a series of functions converging to the exact wave function 7, 8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exponents l i , m i , and n i are nonnegative integers and, along with the nonlinear parameter and the linear parameters c i , these are optimized using the Variation Theorem. The wavefunction that we have used has N ¼ 204 and was developed by Koga et al [10], who showed that it reproduces the exact ground-state energy of the helium atom [11] to within 3 nanohartrees. The intracule of the 204-term Hylleraas wavefunction (7) reduces [12] to …”
Section: Correlated Wavefunction and Intraculementioning
confidence: 99%
“…Recently, they have applied their approach to compute the ground-state energy of the helium atom to an astonishing 43 decimal digits [12] and also to obtain spectacularly accurate energies [13] for its singlet and triplet 1s ns states, for n = 2, 3, . .…”
mentioning
confidence: 99%